Elevated Fibroblast Growth Factor 23 Concentration: Prediction of Mortality among Chronic Kidney Disease Patients - Chathoth, Shahanas; Al-Mueilo, Samir; Cyrus, Cyril; Vatte, Chittibabu; Al-Nafaie, Awatif; Al-Ali, Rudaynah; Keating, Brendan J.; Al-Muhanna, Fahad; Al Ali, Amein (Cardiorenal medicine, 2015)
Background: The osteocyte-derived hormone, fibroblast growth factor 23 (FGF23), regulates the phosphorus metabolism and suppresses 1,25-dihydroxyvitamin D production, thereby mitigating hyperphosphatemia in patients with renal disorders. An elevated FGF23 level is suggested to be an early biomarker of altered phosphorus metabolism in the initial stages of chronic kidney disease (CKD) and acts as a strong predictor of mortality in dialysis patients. In the Saudi population, there is no report on the FGF23 level in CKD patients to date. This study aims to estimate the plasma FGF23 levels in the Saudi population and to correlate it with its clinical manifestations in order to ascertain its role in the pathogenesis of CKD patients. Methods: The FGF23 level in the plasma samples was determined using ELISA in a diverse cohort of 89 cases with stage 3-5 CKD and 100 healthy subjects. The plasma FGF23 level was correlated with other biochemical parameters. Results: The results revealed that the FGF23 level was markedly elevated among CKD patients compared to the control group, and a significant inverse correlation was observed between the FGF23 level and glomerular filtration rate. FGF23 elevation was approximately 40-fold among stage 5 patients compared to the control, while the elevation of phosphate, parathyroid hormone (PTH) and alkaline phosphatase was 2-, 3- and 8-fold in this stage, respectively. Conclusion: Elevated FGF23 levels may have a strong correlation with the disease pathogenesis. In addition, FGF23 might be a future therapeutic target to intervene against the progression of CKD as well as to increase patient survivability.